IX. MOVEMENT OF ICE SHEET AND GLACIERS IN SOYA COAST IN 1969-1972 - シミズ, ヒロム; ヨシムラ, アイイチロウ; ナルセ, レンジ; ワタナベ, オキツグ; ナカオ, マサヨシ; オクヒラ, フミオ; SHIMIZU, Hiromu; YOSHIMURA, Aiichiro; NARUSE, Renji; WATANABE, Okitsugu; NAKAWO, Masayoshi; OKUHIRA, Fumio (National Institute of Polar Research, 1975)
P(論文) departmental bulletin paper